EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK DALAM KETERAMPILAN MEMBACA INTENSIF PADA SISWA KELAS III SD NEGERI MONGGANG BANTUL - Indah Putri Ramadhani; C. Indah Nartani (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2018)
Abstract: This research purpose to describing the effectiveness of learning and skills of intensive reading to the student on grade 3rd in Monggang Bantul Elementary School which uses cooperative learning model of talking stick type compared to lecture method. Model cooperative of a talking stick type is a method of learning who uses a stick (talking stick) as a tool to turn the direction to reveal the content of the reading (intensive reading). The type of this research is a quasi-experiment. Data analysis using a testt with the result tarithmetic (1,557) and p = 0,126 who show there is a significant difference between using a method of talking stick learning with lecture method at learning of intensive reading. Seen from the results of average talking stick method has an average 23,4348 while lecturing method has an average 19,6923, with a model of cooperative learning talking stick type effective uses in learning of reading intensive.Â